miR-34c attenuates epithelial-mesenchymal transition and kidney fibrosis with ureteral obstruction - Morizane, Ryuji (Nature Publishing Group, 2014)
micro RNAs (miRNAs) are small non-coding RNAs that act as posttranscriptional repressors by binding to the 3′-UTR of target mRNAs. On the other hand, mesenchymal-epithelial transition (EMT) and kidney fibrosis is a pathological process of chronic kidney disease (CKD), and its relationship to miRNAs is becoming recognized as a potential target for CKD therapies. To find new miRNAs involved in EMT, we examined miRNA expression in experimental models of EMT and renal epithelialization using microarray, and found that miR-34c attenuates EMT induced by TGF-β in a mouse tubular cell line. To confirm the effects of miR-34c in vivo, we administered the precursor of miR-34c to mice with unilateral ureteral obstruction, and miR-34c decreased kidney fibrosis area and the expression of connective tissue growth factor, α-SMA, collagen type 1, collagen type 3 and fibronectin. In conclusion, our study showed miR-34c attenuates EMT and kidney fibrosis of mice with ureteral obstruction.